Evaluation of First Trimester Miscarriage among Sudanese Woman in Khartoum State Using Ultrasonography - Esmeal, Maha Esmeal Ahmed; Khalid, Nagla Hussien Mohamed; Ilkheir, Rehab Hussien; Fathelrahman, Samia Abdelgauom (International Journal of Innovative Research in Medical Science, 2019)
Background: Miscarriage is that the commonest complication of early pregnancy. In recent years, there has been a trend towards more conservative management for women with first trimester miscarriage. Most miscarriages are due to uterine malformations or chromosomal abnormalities, which account for the majority that occur within 10 weeks of gestation. Ultrasonography is that the most popular modality to verify the presence of a viable intrauterine gestation. In some instances, creating an identification of early pregnancy loss is simple and requires restricted testing or imaging. Purpose: the purpose of this study was to evaluate the first trimester miscarriage among Sudanese women in Khartoum state using ultrasonography. Methods: descriptive prospective across sectional study conducted in Khartoum state hospitals during period from June 2017 to June 2018 using ultrasound. Out of 100 patients whom in the first trimester and accomplishing the exclusion and inclusion criteria included in the study. Results: the results of the study shows that the mean age of pregnant women was 26-± 30 years majority of them between (26-30) years old. (58%) of abortion occur in homemakers occupations groups. Incomplete and complete miscarriage are the most common (34%) and the most common cause of miscarriage was unexplained (80%), trauma (12%), uterine defect (4%), fibroid (2%), febrile diseases (2%). Conclusion: The study concluded that most common type of miscarriage found at Khartoum is incomplete and complete miscarriage. Ultrasound characterized various kinds of miscarriage.